Rationale for criterion of choosing the method for post-harvesting tobacco treating and drying - E. E. Ulyanchenko; E. V. Gnuchikh; N. N. Vinevskaya (Новые технологии)
The choice of the method of drying a particular variety of tobacco is determined by a number of criteria, physiological characteristics of the rate of moisture loss of the variety during drying, production volumes, technological equipment of the production and the desired quality of the obtained raw materials. The aim of the research is to determine the criteria when choosing a method of drying tobacco and justify one of the criteria that determines the method of drying according to the quality indicators of raw materials, using the example of large-leaved skeletal Yubileiny Novyi 142 tobacco variety.  To increase the drying efficiency in post-harvest processing, the method of cutting the costae is used, which allows to halve the drying time. Tobacco is dried in a natural, artificial and combined ways. The raw materials of all drying methods have been evaluated according to the main quality indicators. It has been found that physiological characteristics of the variety make it possible to obtain better raw materials when the combined drying method is used: the yield of raw materials of the first commercial grade is increased to 98%; fiber yield increases; bulk-elastic properties are improved, which reduce specific consumption of raw materials per unit of smoking products; the chemical composition of raw materials improves, toxicity decreases, due to a decrease in nicotine values, fermentation of raw materials increases the smoking advantages of tobacco.